HUBUNGAN SOSIODEMOGRAFI DENGAN KEJADIAN FILARIASIS DI KABUPATEN PEKALONGAN - Riftiana, Nola; Soeyoko, . (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2010)
Background: Glaucoma is characterized by significantly increase in eye pressure that can lead to order eye diseases including part or total blindness. Glaukoma is still the main eye health problem in Indonesia and Yogyakarta Special Teritory. Glaukoma causes permanen blindness. Based on data from medical records of glaucoma patients who seek treatment at hospital outpatient Eye Dr. Yap Yogyakarta in 2009 amounted to 1302 souls, while in the January to May 2010 amounted to 510 souls. This study aims to determine what factors are associated with the incidence of glaucoma in eye hospital Dr. Yap Yogyakarta.Methods: This was observational analytic study using case control design (case control) with a ratio of 1:2. Technique of sampling using the Non-Random Sampling, with purposive sampling approach, with a total sample of 105 respondents consisting of 35 cases and 70 controls, data collected by interview with questionnaire guidelines.Results: test results showed that three variables are not statistically significant and the two variables are statistically significant history of diabetes mellitus (OR = 0.624, p = 0.442, CI 95% = 0.185 to 2.097), history of hypertension (OR = 6.401, p-0, 000, 95% CI = 2.441 to 16.784), eye trauma (OR = 1.130, p = 0.839, CI 95% = 0.348 to 3.666), complication of eye surgery (OR = 3.463, p = 0.004, 95% CI - 1.444 to 8.306), and the use of corticosteroid drugs (OR-1, 130, p = 0.839, CI 95% = 0.348 to 3.666). Results of multivariat test surgery showed that the most dominant variables on the incidence of glaucoma in eye hospital Dr. Yap Yogyakarta is a history of hypertension with Sig = 0.001 Exp [3 = 5.675 (95% CI:2.105 to 15.301).Conclusion: There was two variables that is statistically significant, history of hypertension and complications of eye surgery. The most dominant variable with the incidence of glaucoma was a history of hypertension.Keywords: Glaucoma, Complications, Corticosteroids